Dietary intake of xylose impacts the transcriptome and proteome of tissues involved in xylose metabolism in swine - Huntley, Nichole F.; de Souza, Marcela M.; Schulte, Matthew D.; Beiki, Hamid; de Lima, Andressa O.; Jantzi, Abigail E.; Lonergan, Steven M.; Huff-Lonergan, Elisabeth J.; Patience, John F.; Koltes, James E. (Frontiers in Animal Science, 2023)
Xylose is a primary component of arabinoxylan in swine diets. Since arabinoxylan is a significant component of fiber, and since fiber is generally rising in practical pig diets globally, the study of arabinoxylan and xylose is of increasing interest. However, mechanisms by which free xylose may be absorbed and the pathways impacted by xylose have yet to be elucidated in the pig. The objective of this study was to determine the impact of xylose supplementation on gene expression and protein abundance in jejunum, kidney, liver, and muscle tissues which have previously been identified as possible sites of xylose absorption or metabolism. This study was intended to expand the preliminary understanding of dietary xylose metabolism and utilization in pigs. One study, replicated twice over time with twenty-four total crossbred gilts were used to assess two dietary treatments: xylose-free (0%) control and 8 g D-xylose/kg. The impact of xylose on growth was monitored by measuring initial and final body weight, serum IGF-1, and liver glycogen concentrations. Rate and efficiency of gain were reduced on the xylose diet but not to a level that would occur if xylose was not used at all; the detection of xylose systemically further supports this conclusion. This study confirmed that the pig can utilize dietary xylose. To determine the impact of xylose on tissue metabolism, samples were collected from all four tissues for gene expression analysis by RNA-sequencing and kidney and liver samples were subjected to proteomic analysis by 2D_DIGE and mass spectrometry. The majority of differentially expressed (DE) genes were identified in kidney (n =157) with few identified in the jejunum (n = 16), liver (n = 1) and muscle (n = 20). The DE genes in the kidney were mainly identified as involved in lipid biosynthesis and fatty acid metabolism. Proteomic results corroborated these findings. Although the inclusion of xylose in a diet at practical levels is shown to impact energy metabolic processes, it has been confirmed that this 5-carbon sugar can support growth only slightly below that of glucose, a 6-carbon sugar that is more commonly utilized as an energy source in pig diets.